2020
DOI: 10.1029/2020sw002467
|View full text |Cite
|
Sign up to set email alerts
|

Modified GIC Estimation Using 3‐D Earth Conductivity

Abstract: Geomagnetically induced currents (GICs) are quasi‐direct current (DC) electric currents that flow in technological conductors during geomagnetic storms. Extreme GICs are hazardous to man‐made infrastructure. GICs enter and exit the technological systems, such as the electric power grid, at grounding points, and their magnitudes depend on the currents that flow underground. They are, therefore, a function of the Earth's electrical conductivity, represented at ground level as Earth impedances, as well as the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…If we can accurately model the temporal and spatial characteristics of the surface magnetic field, then useful modeling of GICs should be a straightforward task. This is dependent on knowing the physical properties of the system in question, and possessing a realistic knowledge of the local ground conductivity (Boteler, 2003; Bedrosian & Love, 2015; Pulkkinen et al., 2017; Kelbert & Lucas, 2020). At Mäntsälä, the conductivity is provided by Viljanen, Pulkkinen, et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we can accurately model the temporal and spatial characteristics of the surface magnetic field, then useful modeling of GICs should be a straightforward task. This is dependent on knowing the physical properties of the system in question, and possessing a realistic knowledge of the local ground conductivity (Boteler, 2003; Bedrosian & Love, 2015; Pulkkinen et al., 2017; Kelbert & Lucas, 2020). At Mäntsälä, the conductivity is provided by Viljanen, Pulkkinen, et al.…”
Section: Discussionmentioning
confidence: 99%
“…If we can accurately model the temporal and spatial characteristics of the surface magnetic field, then useful modeling of GICs should be a straightforward task. This is dependent on knowing the physical properties of the system in question, and possessing a realistic knowledge of the local ground conductivity (Boteler, 2003;Bedrosian & Love, 2015;Pulkkinen et al, 2017;Kelbert & Lucas, 2020). At Mäntsälä, the conductivity is provided by Viljanen, Pulkkinen, et al (2006); Viljanen, Tanskanen, et al (2006), and as shown by Equation 1, there is an exact relationship between the geoelectric field and the and GIC (Pulkkinen, Pirjola et al, 2001;Pulkkinen, Viljanen et al 2001) when the geoelectric field is uniform.…”
Section: The Impact On Gic Modelingmentioning
confidence: 99%
“…This Earth-layered model for the European regions has already been used in a number of studies (e.g., Viljanen et al, 2013Viljanen et al, , 2014. Differences concerning various methods were emphasized by (e.g., Viljanen et al, 2012;Kelbert & Lucas, 2020).…”
Section: Calculation Of the Geoelectric Fieldmentioning
confidence: 99%
“…As for the source, approximating it by plane waves still prevails in the GIC-related studies (e.g., Campanya et al, 2019;Kelbert & Lucas, 2020;Kelbert et al, 2017;Lucas et al, 2018;Sokolova et al, 2019;Wang et al, 2020). This approximation seems reasonable in low and middle latitudes, where the main source of anomalous geomagnetic disturbances is a large-scale magnetospheric ring current.…”
Section: Space Weathermentioning
confidence: 99%